2018
DOI: 10.1016/j.earlhumdev.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal stress moderates the link between early and later emotional skills in very preterm-born children: An 11-year-long longitudinal study

Abstract: Although prematurity affects the emotional abilities of preadolescents, the link between emotional skills in early and later childhood is moderated by the severity of perinatal stress. In particular, VPT children who are born with more complications, and as such experience a more stressful perinatal environment, are more likely to show emotional difficulties at preadolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Indeed, numerous studies reported a higher prevalence of internalizing problems in this population with an increased risk for anxiety symptoms, depressive symptoms, and withdrawn behavior (Guedeney et al, 2012; Somhovd et al, 2012; Montagna and Nosarti, 2016). Dimitrova et al (2018) have recently shown that early emotional problems in 18-month-old preterm children predicted later internalizing problems at 11 years of age, but this link was moderated by the severity of perinatal stress. Preterm children who experienced high perinatal stress were at increased risk for emotional difficulties during preadolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies reported a higher prevalence of internalizing problems in this population with an increased risk for anxiety symptoms, depressive symptoms, and withdrawn behavior (Guedeney et al, 2012; Somhovd et al, 2012; Montagna and Nosarti, 2016). Dimitrova et al (2018) have recently shown that early emotional problems in 18-month-old preterm children predicted later internalizing problems at 11 years of age, but this link was moderated by the severity of perinatal stress. Preterm children who experienced high perinatal stress were at increased risk for emotional difficulties during preadolescence.…”
Section: Discussionmentioning
confidence: 99%
“…21-31 A mere 7 studies extended the scope of neonatal stress beyond pain-related stressors by including exposure to all stressors during the NICU stay: the quality of developmental care, medical stressors (such as all potentially stressful events during the NICU stay associated with medical care based on the Neonatal Infant Stressor Scale 3 ), and maternal separation. [32][33][34][35][36][37][38] We did not identify studies fulfilling our inclusion criteria that investigated noise or light exposure as stressors. Two studies addressed both clinical and laboratory or imaging outcomes.…”
Section: Flow Of Studies and Study Characteristicsmentioning
confidence: 99%
“…The developmental stones underlying brain development in humans are highly susceptible to adverse effects and can be modulated by maternal markers transferred vertically during pregnancy. Observational studies show that prenatal adverse environmental effects, such as maternal stress and infections affect fetal neurodevelopment and increase the risk for neurological or psychiatric disorders in future life [4][5][6][7]. Degradation of neurodevelopmental pathways may affect cognitive and mental disorders, as well as affect future brain function and increase the risk of neurodevelopmental and psychiatric disorders in later life [8].…”
Section: Microchimerism Physiopathologymentioning
confidence: 99%